2018
DOI: 10.3389/fpsyg.2018.02160
|View full text |Cite
|
Sign up to set email alerts
|

Conversational Time Travel: Evidence of a Retrospective Bias in Real Life Conversations

Abstract: We examined mental time travel reflected onto individuals’ utterances in real-life conversations using a naturalistic observation method: Electronically Activated Recorder (EAR, a portable audio recorder that periodically and unobtrusively records snippets of ambient sounds and speech). We introduced the term conversational time travel and examined, for the first time, how much individuals talked about their personal past versus personal future in real life. Study 1 included 9,010 sound files collected from 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 92 publications
1
25
0
Order By: Relevance
“…Initially considered a somewhat esoteric "niche-method", it has over the years methodologically matured into a psychometrically established and broadly used ecological assessment method. To date, the EAR method has been successfully employed, with good acceptance and compliance, in a range of healthy and clinical populations (Baddeley Pennebaker & Beevers, 2013;Brown, Tragesser, Tomko, Mehl & Trull, 2014;Hasselmo et al, 2018;Holleran, Whitehead, Schmader & Mehl, 2011;Minor et al 2018;Robbins et al, 2018;Slatcher & Robles, 2012;Tobin et al, 2015) and in age groups ranging from early childhood to A PRACTICAL GUIDE TO CODING AND PROCESSING EAR DATA 4 old age (Alisic, Barrett, Bowles, Conroy & Mehl, 2015;Bollich et al, 2016;Demiray & Martin, 2018).…”
Section: Best Practices For Electronically Activated Recorder (Ear) Rmentioning
confidence: 99%
“…Initially considered a somewhat esoteric "niche-method", it has over the years methodologically matured into a psychometrically established and broadly used ecological assessment method. To date, the EAR method has been successfully employed, with good acceptance and compliance, in a range of healthy and clinical populations (Baddeley Pennebaker & Beevers, 2013;Brown, Tragesser, Tomko, Mehl & Trull, 2014;Hasselmo et al, 2018;Holleran, Whitehead, Schmader & Mehl, 2011;Minor et al 2018;Robbins et al, 2018;Slatcher & Robles, 2012;Tobin et al, 2015) and in age groups ranging from early childhood to A PRACTICAL GUIDE TO CODING AND PROCESSING EAR DATA 4 old age (Alisic, Barrett, Bowles, Conroy & Mehl, 2015;Bollich et al, 2016;Demiray & Martin, 2018).…”
Section: Best Practices For Electronically Activated Recorder (Ear) Rmentioning
confidence: 99%
“…Prior laboratorybased research has extensively studied how the sharing of autobiographical memories appears to change with older age, with one key finding being that there is a robust age-related reduction in episodic memories that is evident in both the frequency at which such memories are retrieved (Ford et al, 2014;Piolino et al, 2006;Ros et al, 2009Ros et al, , 2017 and how much episodic detail is shared to describe unique life events (Addis et al, 2008;Devitt et al, 2017;Gaesser et al, 2011;Levine et al, 2002). The present study utilized the EAR, a method that has recently been applied to capture memories being shared in everyday conversations as they happen (Brianza & Demiray, 2019;Demiray et al, 2018;2019), in order to extend the assessment of episodic specificity out of the laboratory and shed light on how older age and episodic specificity are related in the real-world.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the EAR has been applied to assess autobiographical sharing in natural, everyday social life, revealing outcomes that replicate and go beyond findings from the laboratory. For instance, prior work using the EAR has shown that in everyday social interactions, older adults tend to be past-oriented (Demiray et al, 2018) and share fewer future thoughts than young adults (Brianza & Demiray, 2019). Older adults also appear to share autobiographical memories in their natural social relationships for specific motives .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For humans, however, the past seems to have a special status independent from what it tells us about the future. This fact becomes particularly apparent in conversational behavior where people have been found to display a "retrospective bias" by talking two to three times more often about the past than the future (Demiray et al 2018). Some consequences of the ability to represent time should have generated evolutionary pressure for the ability to represent the past in its own right, independently from its benefits for future-directed cognition.…”
Section: Introductionmentioning
confidence: 99%